Play and Literacy in Early Childhood Classrooms - Munger, Elizabeth Ann (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
Recent research shows that play is being replaced in early childhood classrooms by direct instruction, due to academic accountability and other pressures. This manuscript shares some of the many benefits of play in the classroom on young children. Many recent studies have shown that play is a developmentally appropriate way to teach and practice literacy skills with early childhood students, while helping them to become successful emergent readers. This article will examine different ways that play can be used to instruct and reinforce literacy skills with emergent and at-risk readers.